Third CoreValve™ insertion for treatment of a severe paravalvular leak after a failed valve-in-valve procedure. (1st June 2015) - Estévez-Loureiro, Rodrigo; Cuellas, Carlos; Gualis, Javier; de Prado, Armando Pérez; Castaño, Mario; Soria, Carlos; Alonso, David; Garrote, Carmen; Rodríguez, Miguel Ángel; Fernández-Vázquez, Felipe
Abstract: An 83-year-old high-risk gentleman diagnosed with severe symptomatic aortic stenosis was scheduled for TAVR. A 31 mm CoreValve was implanted but severe paravalvular leak was noted. A valve-in-valve procedure was performed. However, the valve frame was partially dislodged into de ascending aorta. We report our strategy to solve this severe leak after a failed valve-in-valve procedure.